Parental Influence on Radicalization and De-radicalization according to the Lived Experiences of Former Extremists and their Families - de Winter, Micha (Journal for deradicalization, 2017)
EU member-states target families in order to prevent or counter radicalization. However, there is little empirical knowledge to confirm that parents influence the radicalization and de-radicalization process. Because there is little known about the role that parents play in radicalization and de-radicalization, this qualitative study explored the family dynamics in these processes together with 11 former radicals and their families. The study consists of 21 in-depth interviews with Dutch former radicals and their family members and it was found that formers and their families do not recognize a direct influence of parents on radicalization and de-radicalization. However, a more indirect influence seems to be in place: a (problematic) family situation may influence the radicalization process and family support can possibly play a role in de-radicalization. It is also stressed that parents have need for knowledge about the different ideologies and for tools on how to respond to their children’s radicalization. Family support programs could focus on these lacunas in order to help families counter radicalization